Activation of TRPV1 attenuates high salt‐induced cardiac hypertrophy through improvement of mitochondrial function. (12th January 2015) - Lang, Hongmei; Li, Qiang; Yu, Hao; Li, Peng; Lu, Zongshi; Xiong, Shiqiang; Yang, Tao; Zhao, Yu; Huang, Xiaohu; Gao, Peng; Zhang, Hexuan; Shang, Qianhui; et al.
Abstract : Background and Purpose: High‐salt diet induces cardiac remodelling and leads to heart failure, which is closely related to cardiac mitochondrial dysfunction. Transient receptor potential (TRP) channels are implicated in the pathogenesis of cardiac dysfunction. We investigated whether activation of TRP vanilloid (subtype 1) (TRPV1) channels by dietary capsaicin can, by ameliorating cardiac mitochondrial dysfunction, prevent high‐salt diet‐induced cardiac hypertrophy. Experimental Approach: Male wild‐type (WT) and TRPV1 −/− mice were fed a normal or high‐salt diet with or without capsaicin for 6 months. Their cardiac parameters and endurance capacity were assessed. Mitochondrial respiration and oxygen consumption were measured using high‐resolution respirometry. The expression levels of TRPV1, sirtuin 3 and NDUFA9 were detected in cardiac cells and tissues. Key Results: Chronic high‐salt diet caused cardiac hypertrophy and reduced physical activity in mice; both effects were ameliorated by capsaicin intake in WT but not in TRPV1 −/− mice. TRPV1 knockout or high‐salt diet significantly jeopardized the proficiency of mitochondrial Complex I oxidative phosphorylation (OXPHOS) and reduced Complex I enzyme activity. Chronic dietary capsaicin increased cardiac mitochondrial sirtuin 3 expression, the proficiency of Complex I OXPHOS, ATP production and Complex I enzyme activity in a TRPV1‐dependent manner. Conclusions and Implications: TRPV1 activation by dietary capsaicin can antagonize high‐salt diet‐mediated cardiac lesions by ameliorating its deleterious effect on the proficiency of Complex I OXPHOS. TRPV1‐mediated amendment of mitochondrial dysfunction may represent a novel target for management of early cardiac dysfunction. Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23